Malaria: Overview of the Global Situation and Problems in Asia - Sumarmo Sumarmo (Indonesian Pediatric Society, 1989)
The overall world malaria situation has remained static in recent years, but the disease continues to be a major public health problem in endemic countries. Of a total world population of 4818 millions in 1985, about 2316 millions (48%) live in areas where antimalarial measures are carried out. About 405 millions Â people inhabit areas where no specific measures are undertaken to control malaria transmission, and the prevalence of malaria remains virtually unchanged.In Asia west of India. 186 out of 222 millions people live in originally malarious areas. Fifteen million people live in areas which have been freed from the disease, and 35 millions in areas with limited risk. About 4 millions people ore not protected by specific antimalarial measures. In Middle South Asia with a total population of about 884 millions. 850 millions (96%) are exposed to malaria risk of varying degrees. With the exception of a small area in Nepal, all originally malarious areas are included under malaria control operations. Of a total population of 1670 millions in the East Asia and Oceania region, 1324 millions live in originally malarious areas. Malaria has been eradicated from areas where 144 millions live, and the risk in considered to be limited in areas with a population of 531 millions.In view of the goal of health for all by the year 2000, malaria control programs must be on important part of the overall health program in malarious countries. These programs would require participation of many different disciplines, including some not specifically related 10 health care. This must be done with an understanding of malaria epidemiology and the local ecological situation, and tailored to economic reality in the malarious region being considered.